Exploring the process of restoring psychological needs after incidences of frustration and need unfulfillment - Dalgas, Birgitte Westerskov; Ntoumanis, Nikos; Elmose-Østerlund, Karsten; Bredahl, Thomas Viskum Gjelstrup (Frontiers in Psychology, 2024)
Background: Research on psychological need restoration after incidences of need frustration holds promise for deepening our understanding of the dynamic nature of psychological needs proposed by self-determination theory. We aimed to extend this work by exploring differences in the process of restoring psychological needs after indences of frustration versus need unfulfillment. Methods: Indepth semi-structured interviews were conducted with 42 Danish adults varying in age, gender, and physical activity levels. Data were analyzed using the Framework Method. Results: We identified four distinct yet interconnected phases in the need restoration process: Discrepancies between Actual and Desired Need States, Experiencing Negative Emotions, Initiating Plans for Action, and Action Stage. These stages offer a comprehensive framework for understanding how individuals restore their needs. Discussion: We discerned contrasting approaches to need restoration depending on prior experiences of need frustration due to external contingencies versus need frustration due to internal factors and need unfulfillment. Need frustration due to external contingencies prompts withdrawal, aligning with the avoidance strategies identified in the literature. Conversely, unfulfilled needs and need frustration due to internal factors lead to proactive engagement, highlighting a distinct 'fight' response. These insights extend existing research, providing a nuanced understanding of the dynamic processes of need restoration.